(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2023)
Abstract Expressionism is an art form that began in the West and later gained influence in the East. In the years after World War II, Abstract Expressionism became the catalyst in the transition of modern art in Asia. In Malaysia, with the advocacy of Abstract Expressionism and the spirit of Expressionism, abstract art became mainstream in the art scene since the 1950s. Abstract Expressionism from two different worlds—America and/or Europe and Malaysia—is different, especially in terms of the artists’ respective approach and creativity. This article discusses how the evolution of abstraction works through the artworks produced by Syed Ahmad Jamal, Yeoh Jin Leng, Latiff Mohidin, and Chew Teng Beng. This is followed by a discussion on the diversity of abstraction forms in Malaysian Abstract Expressionist art through the study of works by the aforementioned artists. Full text: PDF